A matter of perspective – Objective versus subjective outcomes in the assessment of quality of recovery. Issue 3 (September 2018) - Bowyer, Andrea; Royse, Colin
Abstract : Current post-operative recovery assessment exists as a dichotomy, maintaining objectivity whilst providing relevance to patient-centred care. Both objective and subjective measures are utilised in modern recovery assessment and are best viewed as complimentary. At institutional and provider levels, performance indicators are utilised as surrogates for quality of recovery but only if these indicators are assessed in the clinical context from which they are derived. Patient-reported outcomes prioritise the patient's perspective of symptoms and care, which are the most important aspects at the time of assessment but are limited by their susceptibility to response shift and recall bias. Ideally, quality of recovery is assessed using objective measures in concert with measures of clinical complexity and in parallel with patient-reported outcomes.